Pyroptosis: A New Insight Into Eye Disease Therapy - Zhang, Yun; Jiao, Yan; Li, Xun; Gao, Sheng; Zhou, Nenghua; Duan, Jianan; Zhang, Meixia (Frontiers in Pharmacology, 2021)
Pyroptosis is a lytic form of programmed cell death mediated by gasdermins (GSDMs) with pore-forming activity in response to certain exogenous and endogenous stimuli. The inflammasomes are intracellular multiprotein complexes consisting of pattern recognition receptors, an adaptor protein ASC (apoptosis speck-like protein), and caspase-1 and cause autocatalytic activation of caspase-1, which cleaves GSDMD, inducing pyroptosis accompanied by cytokine release. In recent years, the pathogenic roles of inflammasomes and pyroptosis in multiple eye diseases, including keratitis, dry eyes, cataracts, glaucoma, uveitis, age-related macular degeneration, and diabetic retinopathy, have been continuously confirmed. Inhibiting inflammasome activation and abnormal pyroptosis in eyes generally attenuates inflammation and benefits prognosis. Therefore, insight into the pathogenesis underlying pyroptosis and inflammasome development in various types of eye diseases may provide new therapeutic strategies for ocular disorders. Inhibitors of pyroptosis, such as NLRP3, caspase-1, and GSDMD inhibitors, have been proven to be effective in many eye diseases. The purpose of this article is to illuminate the mechanism underlying inflammasome activation and pyroptosis and emphasize its crucial role in various ocular disorders. In addition, we review the application of pyroptosis modulators in eye diseases.